Muscle or Motivation? A Stop-Signal Study on the Effects of Sequential Cognitive Control - Huizenga, Hilde M.; van der Molen, Maurits W.; Bexkens, Anika; Bos, Marieke G.; Van Den Wildenberg, Wery P. (Frontiers in Psychology, 2012)
Performance in cognitive control tasks deteriorates when these tasks are performed together with other tasks that also require cognitive control, that is, if simultaneous cognitive control is required. Surprisingly, this decrease in performance is also observed if tasks are preceded by other cognitive control tasks, that is, if sequential cognitive control is required. The common explanation for the latter finding is that previous acts of cognitive control deplete a common resource, just like a muscle becomes fatigued after repeated use. An alternative explanation however has also been put forward, namely that repeated acts of cognitive control reduce the motivation to match allocated resources to required resources. In this paper we formalize these two accounts, the muscle and the motivation account, and show that they yield differential predictions on the interaction between simultaneous and sequential cognitive control. Such an interaction is not predicted by the muscle account, whereas it is predicted by the motivation account. These predictions were tested in a paradigm where participants had to perform a series of stop-signal tasks, these tasks varied both in their demands on simultaneous control and in their demands on sequential control. This paradigm, combined with a multilevel analysis, offered the possibility to test the differential predictions directly. Results of two studies indicate that an interaction between simultaneous and sequential cognitive control is present. Therefore it is concluded that effects of sequential cognitive control are best explained by the motivation account.